Extensible statistical software: on a voyage to Oberon - Sawitzki, Günther (Journal of computational and graphical statistics, 1996)
Recent changes in software technology have opened new possibilities for statistical computing. Conditions for creating efficient and reliable extensible systems have been largely improved by programming languages and systems that provide dynamic loading and type-safety across module boundaries, even at run time. We introduce Voyager, an extensible data analysis system based on Oberon, which tries to exploit some of these possibilities.